2012
DOI: 10.1002/jsfa.5966
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gender (barrows vs. females) on carcass traits and meat quality of Celta pig reared outdoors

Abstract: Values for carcass parameters indicated that Celta pigs produced very similar carcasses to those obtained from other rustic pigs. The percentage of 'noble' cuts relative to carcass weight was higher in barrows than in females. Finally, gender appeared to have little effect on the colour, textural organoleptic traits or amino acid profile of this breed of pig.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
15
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 34 publications
9
15
1
Order By: Relevance
“…Killing out values (around 85%) were higher than those reported in other studies carried out on improved breeds and their crosses (Blasco et al, 1994;García-Macías et al, 1996;Correa et al, 2006;Flores-Rondón et al, 2009) and also higher than those reported for Celta pigs slaughtered at an age of 12 months (Franco & Lorenzo, 2013). This was probably due to the high live weights of the pigs in the present study, as killing out values are widely reported to increase with the live a-b Means within the same row (corresponding to the same trait) not followed by a common letter, differ significantly (p < 0.05).…”
Section: Carcass Traitscontrasting
confidence: 60%
See 2 more Smart Citations
“…Killing out values (around 85%) were higher than those reported in other studies carried out on improved breeds and their crosses (Blasco et al, 1994;García-Macías et al, 1996;Correa et al, 2006;Flores-Rondón et al, 2009) and also higher than those reported for Celta pigs slaughtered at an age of 12 months (Franco & Lorenzo, 2013). This was probably due to the high live weights of the pigs in the present study, as killing out values are widely reported to increase with the live a-b Means within the same row (corresponding to the same trait) not followed by a common letter, differ significantly (p < 0.05).…”
Section: Carcass Traitscontrasting
confidence: 60%
“…This shows a particular characteristic of the Celta pig, already described (Franco & Lorenzo, 2013), and other unimproved breeds, i.e. long legs adapted to walking, as a consequence of outdoor exploitation in extensive systems.…”
Section: Semimembranosussupporting
confidence: 54%
See 1 more Smart Citation
“…Meat from gilts had higher thawing and cooking losses than that from barrows, which agrees with previous results (Latorre et al, 2008;Franco and Lorenzo, 2013). The lower water holding capacity of gilt loin would justify, at least in part, its greater hardness, as a negative relationship between both traits has been reported (Tomovic et al, 2014).…”
Section: Or Nosupporting
confidence: 90%
“…Therefore, the higher revenue from a barrow carcass will compensate the higher feeding costs compared with a gilt carcass. Also, carcasses from barrows were longer and had heavier lean cuts (hams, shoulders and loins) than those from gilts confirming previous results with similar pigs (Rodríguez-Sánchez et al, 2011) and autochthonous breeds reared outdoor (Franco and Lorenzo, 2013). However, when both sexes are slaughtered at similar BW, gilts have longer carcasses and heavier trimmed lean pieces (Latorre et al, 2009;Suárez-Belloch et al, 2016), probably because females are leaner.…”
Section: Carcass Characteristicssupporting
confidence: 85%